Exploring the determinants of fruits and vegetables consumption among adults in Saudi Arabia: integrating habit strength in theory of planned behavior - Aljehany, Buthaina M.; Aljadani, Haya; Abusalih, Howeida; Abduljawad, Eman A. (Frontiers in Nutrition, 2025)
IntroductionFruit and vegetable consumption is low among adults in Saudi Arabia.AimTo identify the main determinants of fruit and vegetable consumption among Saudi adults and to suggest possible intervention strategies to promote healthier eating habits.MethodsA cross-sectional study was conducted with a sample of Saudi adult students (n = 471), using the Theory of Planned Behavior (TPB) as a conceptual framework. Structural equation modeling (SEM) was used to test the TPB predictors for consuming the recommended five servings of fruits and vegetables per day in the upcoming week, and multi-group analysis was conducted to assess the moderating effect of habits.ResultsThe findings indicate that both the average daily servings and the frequency of meeting the recommended five servings per day are notably low. Higher fruit and vegetable consumption habits are associated with better knowledge, healthier dietary practices, and more consistent physical activity. Perceived Behavioral Control (PBC) emerged as a significant predictor of fruit and vegetable consumption behavior among individuals with low consumption habits.ConclusionFruit and vegetable consumption is influenced by both intention and PBC, with individual habits being an important consideration. To increase fruits and vegetables intake, interventions should be tailored based on the individual’s level of habit.